Dynamic Molecular Processes Detected by Microtubular Opto‐chemical Sensors Self‐Assembled from Prestrained Nanomembranes. (1st March 2013) - Ma, Libo; Li, Shilong; Quiñones, Vladimir A. Bolaños; Yang, Lichun; Xi, Wang; Jorgensen, Matthew; Baunack, Stefan; Mei, Yongfeng; Kiravittaya, Suwit; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> Opto‐chemical sensors are prepared by self‐assembly of SiO/SiO2 nanomembranes into microtube structures. Dynamic molecular processes of H2O and C2H5OH are detected on the surface of sub‐wavelength‐thin nanomembranes. Based on the perturbation theory, quantitative information of molecule layer changes is acquired. The nanomembrane‐based molecular‐sensing ability constitutes a versatile platform for the detection of diverse surface phenomena in a label‐free fashion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>